Upaya Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPA pada Materi Penggolongan Tumbuhan dengan Pembelajaran Cooperatif Model Jigsaw - Siti Umiyati; Ngatiyem Ngatiyem; Sumarni Sumarni; Sukijah Sukijah; Basuki Ernawati; Nunung Nurhayati (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
The background of this research problem is the teacher's effort in realizing the goals of school education, namely developing strategies to create a pleasant learning situation. As for the problems found with regard to the teaching and learning process, especially in science learning related to plant classification material which shows that the level of student mastery is still low. This study aims to improve the learning outcomes of third grade elementary school students on the concept of classifying plants with the jigsaw model cooperative method. The implementation of this learning improvement research was carried out in class III SDN Cipondoh I, Cipondoh District, Tangerang City, totaling 36 people consisting of 18 boys and 18 girls. The results of the final learning test obtained in this study for each cycle have increased. In Cycle I activities, the test results obtained an average of 67 this value is less than the KKM value but in Cycle II activities with an average of 88 more than the KKM value. This research can be concluded that the learning activities arranged using the Jigsaw model cooperative method provide a teaching experience for teachers and a learning experience for students. The researcher teaches the material on classifying plants in class III through 2 stages, namely Cycle I and Cycle II. Keywords: improve student learning outcomes, Jigsaw Model cooperative learning, science.